2010
DOI: 10.3109/02688690903536595
|View full text |Cite
|
Sign up to set email alerts
|

Financial and clinical governance implications of clinical coding accuracy in neurosurgery: A multidisciplinary audit

Abstract: Clinical coding is the translation of documented clinical activities during an admission to a codified language. Healthcare Resource Groupings (HRGs) are derived from coding data and are used to calculate payment to hospitals in England, Wales and Scotland and to conduct national audit and benchmarking exercises. Coding is an error-prone process and an understanding of its accuracy within neurosurgery is critical for financial, organizational and clinical governance purposes. We undertook a multidisciplinary a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 10 publications
0
21
0
Order By: Relevance
“…Most debate around HES data quality concerns the primary and secondary diagnostic and procedure field. [36][37][38][39] Nonetheless, a recent systematic review of discharge coding accuracy in routine UK data found that primary diagnosis accuracy has improved from 73.8% to 96.0% in the 10 years since the introduction of Payment by Results. 40 Not all delivery records contain supplementary information, although the percentage of records with a complete maternity tail has improved over time.…”
Section: Discussionmentioning
confidence: 99%
“…Most debate around HES data quality concerns the primary and secondary diagnostic and procedure field. [36][37][38][39] Nonetheless, a recent systematic review of discharge coding accuracy in routine UK data found that primary diagnosis accuracy has improved from 73.8% to 96.0% in the 10 years since the introduction of Payment by Results. 40 Not all delivery records contain supplementary information, although the percentage of records with a complete maternity tail has improved over time.…”
Section: Discussionmentioning
confidence: 99%
“…Most debates around HES data quality concern the primary and secondary diagnostic and procedure field. 9,[44][45][46] Nonetheless, a recent systematic review of discharge coding accuracy in routine UK data found that primary diagnosis accuracy has improved from 73.8% to 96.0% in the 10 years since the introduction of Payment by Results. 47 Not all delivery records contain supplementary information, although the percentage of records with a complete maternity tail has improved over time.…”
Section: Data Qualitymentioning
confidence: 99%
“…This supports previous work that has shown clinician input to have similar beneficial effects. 19,20 However, such benefits are not only limited to financial rewards. 11,15,19,20 Accurate coding also offers benefit towards hospital governance, in terms of understanding the underlying activity so that resources may be better allocated and organised.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 However, such benefits are not only limited to financial rewards. 11,15,19,20 Accurate coding also offers benefit towards hospital governance, in terms of understanding the underlying activity so that resources may be better allocated and organised. 11,19,20 Similarly, there are wider implications, at national and international level, 15 as such codes are also used to estimate disease incidence and prevalence along with temporal and geographical variation.…”
Section: Discussionmentioning
confidence: 99%